PRINSIP PARTISIPASI DAN SOLIDARITAS DALAM VISI PERSONALISTIK KAROL WOJTYLA - Aloysius Widyawan Luis (Arete, 2013)
Solidarity is not only about someone's personal sympathy with his neighbor. It is rooted in his personal and human values. Even it is not based on any similarity of common views, purpose or goals of life, or even primordialism. It is about values, humanity, and person. In the experience of each human life, self-consciousness allows each self to be conscious also of the other self that is the same and equal to himself. The other self is certainly enmeshed in my life and my-self is enmeshed in his life. This enmeshing or participation embraces all the dimensions of the human being as a person. It does not involve only some dimensions of human life. This enmeshment or participation is also not merely discourse or consciousness but rather manifests itself in concrete action because, in principle, it is only in action that we can acquire a complete knowledge of who man is as a person. Within the scope of social life, participation is the key to solidarity between self and the other self so that together they head towards the common good or bonum commune. Thus, there is no true solidarity if it is not geared towards the bonum commune